Exploring the motivations behind misreporting self-measured blood glucose in adolescents with type 1 diabetes – a qualitative study. Issue 1 (December 2015) - Blackwell, Miranda; Tomlinson, Paul; Rayns, Jenny; Hunter, Jackie; Sjoeholm, Annika; Wheeler, Benjamin
Abstract Background Despite advances in diabetes management, the reporting and self-monitoring of blood glucose (SMBG) remains fundamental. While previous work has established that the misreporting of SMBG to family and medical professionals is surprisingly common, the motivations behind this behaviour have never been examined. We aimed to investigate the motivations behind misreporting of SMBG in adolescents with type 1 diabetes (T1DM). Methods Fifteen semi-structured interviews were conducted with adolescents (aged 12–19 inclusive) with T1DM recruited through diabetes clinics across the Otago/Southland region of New Zealand from November 2015 to January 2016. These were transcribed and content analysis performed to identify themes and subthemes in misreporting behaviour. Results The mean age of participants was 15.7 years, 60 % were male, with 67 % using multiple daily insulin injections, and 33 % on insulin pumps. Their median HbA1c was 84 mmol/mol, range 52–130. Misreporting behaviour was described for both electronic pump records and written logbooks, as well as verbally. Multiple motivations for misreporting were given, spanning three major themes: Achieving potential benefits; the avoidance of negative consequences; and the avoidance of worry/concern (in self or in others). The main suggestion of participants to reduce misreporting behaviour was to reduce the negative reactions of others to suboptimal blood glucose readings. Conclusion Electronic, written, and verbal SMBG misreporting remains common. This study provides deeper insight into the motivations leading to this behaviour in adolescents, suggesting that further understanding and attention to this aspect of adherence may lead to improvements not only in glycaemic control and safety, but also to the psychological wellbeing of those with T1DM.